Performance studies on a forced convection solar dryer integrated with a paraffin wax–based latent heat storage system. (June 2017) - Rabha, D.K.; Muthukumar, P.
Highlights: Energy and exergy analyses of solar dryer with a latent heat storage is presented. Drying time of red chilli in solar dryer was reduced by 55% than open sun drying. Latent heat storage provide an extended drying time of 2 h beyond the sunshine. The specific energy consumption of chilli was 6.81 kW h/kg of moisture. Overall efficiency of the drying system was 10.8%. Abstract: This manuscript presents the performance studies on a forced convection solar dryer integrated with a paraffin wax-based shell and tube latent heat storage unit. The solar dryer consists of two double-pass solar air heaters, a paraffin wax-based shell and tube latent heat storage module, a blower, and a drying chamber. The dryer was tested by drying 20 kg of red chilli in the drying air temperature range of 36–60 °C. The initial average moisture content of the chilli was 73.5% (w.b.) and was reduced to the final moisture content of 9.7% (w.b.) in 4 consecutive days. The dryer was operated daily for 10 h from 8:00 h to 18:00 h. The performance of each component of the drying system was evaluated using energy and exergy analyses. The average energy and exergy efficiency of the first solar heater were found to be 32.4% and 0.9%, respectively while for the second solar heater connected in the series with the first one were 14.1% and 0.8%, respectively. The energy and exergy efficiency of the latent heat storage unit were in the range of 43.6–49.8% and 18.3–20.5%, respectively. The exergy efficiency of the drying chamber was found to be between 24.6% and 98.1% with an average of 52.2%. The specific energy consumption of the chilli and the overall efficiency of the drying system were 6.8 kW h per kg of moisture and 10.8%, respectively. The electrical energy consumption of the dryer was 0.7 kW h per kg of moisture which was only 10.3% of the specific energy consumption of the chilli.